Formation of tissue factor-factor VIIa-factor Xa complex prevents apoptosis in human breast cancer cells - Jiang, Xiaofeng; Guo, Yan Lin; Bromberg, Michael E. (Thrombosis and Haemostasis, 2006)
Summary Tissue factor (TF) is a transmembrane glycoprotein that initiates blood coagulation when complexed with factorVIIa (FVIIa).TF is constitutively expressed ina variety of tumor cells and has been shown to playa role in cellular signaling and tumor progression. In this study, we investigated the effect of TF-FVIIa mediated signaling on apoptosis in human breast cancer cells. Apoptosis was induced by prolonged serum starvation and studied using the Adr-MCF-7 cell line, which has high endogenous TF expression. Treatment of the cells with the combination of FVIIa (10 nM) and FX (150 nM), reduced apoptosis by nearly 50% compared with untreated, control cells using an ELISA that detects histone-DNA fragments. In contrast, FVIIa (10 nM) alone did not significantly prevent apoptosis. Pretreatment of the Adr-MCF-7 cells with hirudin, a specific thrombin inhibitor, did not inhibit the anti-apoptotic effect of the combination of FVIIa and FX, whereas this effect could be abrogated by inhibition of phosphorylation of either p44/42 mitogen-activated protein kinase (MAPK) or protein kinaseB (PKB/Akt). In addition, treatment of theAdr-MCF-7 cells with the combination of FVIIa and FX led to a 30-50% increase in the level of the anti-apoptotic protein, survivin, compared with untreated cells usingWestern blot analysis. These results indicate that formation of TF-FVIIa-FXa complex prevents apoptosis in breast cancer cells by a thrombin-independent pathway. Moreover, the anti-apoptotic effect of this signaling pathway involves phosphorylation of both p44/42 MAPK and PKB/Akt and might be mediated in part by an increase in cell survivin levels.
Keywords: Apoptosis; breast cancer; factor VIIa; factor Xa; tissue factor